2003
DOI: 10.1002/cncr.11772
|View full text |Cite
|
Sign up to set email alerts
|

Definitive radiotherapy alone or combined with a planned neck dissection for squamous cell carcinoma of the pharyngeal wall

Abstract: BACKGROUND. In the current study,the authors analyzed the results of definitive radiotherapy for squamous cell carcinoma of the pharyngeal wall. METHODS. Between 1964 and 2000, 148 patients were treated with definitive radiotherapy. All patients had a 2-year minimum follow-up. RESULTS. The following 5-year rates of local and ultimate local control were obtained: T1 disease, 93% and 93%; T2 disease, 82% and 87%; T3 disease, 59% and 61%; and T4 disease, 50% and 50%, respectively. Multivariate analysis revealed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2006
2006
2017
2017

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 35 publications
2
9
0
Order By: Relevance
“…Despite advances in diagnosis and treatment techniques, the treatment outcome of this subsite of head and neck cancer remains relatively poor compared with cancers of other head and neck subsites . Most patients are initially diagnosed with advanced disease (70% of patients with T3–T4 disease in our study) because of the absence of symptoms at an early stage and the richness of submucosal lymphatics in the posterior pharyngeal wall.…”
Section: Discussionmentioning
confidence: 83%
See 1 more Smart Citation
“…Despite advances in diagnosis and treatment techniques, the treatment outcome of this subsite of head and neck cancer remains relatively poor compared with cancers of other head and neck subsites . Most patients are initially diagnosed with advanced disease (70% of patients with T3–T4 disease in our study) because of the absence of symptoms at an early stage and the richness of submucosal lymphatics in the posterior pharyngeal wall.…”
Section: Discussionmentioning
confidence: 83%
“…Squamous cell carcinoma (SCC) of the posterior pharyngeal wall is a relatively rare location in pharyngeal SCC, accounting for 12% to 20% of this sublocation . Despite the lack of prospective comparison, radiotherapy (RT) — alone or associated with concomitant chemoradiotherapy (CRT) — and surgery have both been utilized to treat this type of cancer.…”
Section: Introductionmentioning
confidence: 99%
“…Comparable data regarding gastrostomy tube dependence rates are limited because the number of prospective trials in this patient population is few with many do not report this measure. 3,4,20 Nevertheless, from retrospective reviews, it appears that the long-term rate of feeding tube requirement is similar, 17,19 with the notable exception of the study by Fein et al, 14 who reported on 490 patients treated with radiotherapy alone for oropharyngeal primary tumors and noted permanent gastrostomy tubes in only two patients. In our cohort, similar to reports by other groups, [24][25][26] patients with hypopharyngeal and laryngeal primary tumors were at greatest risk for swallowing dysfunction after CRT.…”
Section: Discussionmentioning
confidence: 99%
“…However, even for T2-3 tumors, significant dysfunction can result, and although organ-preserving surgical techniques have been described, their application is limited by operator expertise and the need for appropriate patient selection. Furthermore, RT without primary surgery in resectable intermediate-stage patients has yielded local control rates comparable to those from surgery followed by RT, [14][15][16][17] especially if hyperfractionated RT is administered. 18 In fact, a retrospective review of North American trials suggested an advantage to RT as primary therapy followed by neck dissection with respect to treatment complications and functional outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Definitive RT has been the preferred treatment of patients with oropharyngeal and pharyngeal wall carcinomas, so that most of the patients with pharyngeal tumors had lesions arising in the pyriform sinus. [11][12][13] All living patients had a minimum follow-up of 2 years. Four patients who were continuously disease-free were lost to follow-up and censored from further analysis at 2.2, 3.1, 8.3, and 13.7 years, respectively.…”
Section: Methodsmentioning
confidence: 99%